Reliability of FEV1/FEV6 to Diagnose Airflow Obstruction Compared with FEV1/FVC: the PLATINO Longitudinal Study - Perez-Padilla, Rogelio (2013)
QUESTION: A 6-second spirometry test is easier than full exhalations. We compared the reliability of the ratio of the Forced expiratory volume in 1 second/Forced expiratory volume in 6 seconds (FEV1/FEV6) to the ratio of the FEV1/Forced vital capacity (FEV1/FVC) for the detection of airway obstruction.METHODS: the PLATINO population-based survey in individuals aged 40 years and over designed to estimate the prevalence of post-Bronchodilator airway obstruction repeated for the same study participants after 5-9 years in three Latin-American cities.RESULTS: Using the FEV1/FVC<Lower limit of normal (LLN) index, COPD prevalence apparently changed from 9.8 to 13.2% in Montevideo, from 9.7 to 6.0% in São Paulo and from 8.5 to 6.6% in Santiago, despite only slight declines in smoking prevalence (from 30.8% to 24.3%). These changes were associated with differences in Forced expiratory time (FET) between the two surveys. in contrast, by using the FEV1/FEV6 to define airway obstruction, the changes in prevalence were smaller: 9.7 to 10.6% in Montevideo, 8.6 to 9.0% in São Paulo, and 7.5 to 7.9% in Santiago. Changes in the prevalence of COPD with criteria based on FEV1/FVC correlated strongly with changes in the FET of the tests (R-2 0.92) unlike the prevalence based on a low FEV1/FEV6 (R-2 = 0.40).CONCLUSION: the FEV1/FEV6 is a more reliable index than FEV1/FVC because FVC varies with the duration of the forced exhalation. Reporting FET and FEV1/FEV6, LLN helps to understand differences in prevalence of COPD obtained from FEV1/FVC-derived indices.